Differences by cognitive impairment in detailed processes for basic activities of daily living in older adults with dementia. Issue 6 (2nd October 2022) - Shimokihara, Suguru; Tabira, Takayuki; Hotta, Maki; Tanaka, Hiroyuki; Yamaguchi, Tomoharu; Maruta, Michio; Han, Gwanghee; Ikeda, Yuriko; Ishikawa, Tomohisa; Ikeda, Manabu
Abstract : Background: Impairment of activities of daily living in patients with dementia has a fundamental and lasting impact on their quality of life and requires a detailed assessment. This study investigated to clarify characteristic of basic activities of daily living (BADL) processes with the severity of cognitive impairment in community‐dwelling older adults with dementia using the Process Analysis of Daily Activity for Dementia (PADA‐D). Methods: Participants were recruited from outpatient departments of 24 hospitals, daycare centres, and home rehabilitation services in Japan. The severity of cognitive impairment was determined using the Mini‐mental State Examination (mild: score ≥ 20; moderate: 10 ≤ score < 20; severe: score < 10). Patient's BADL were assessed according to the PADA‐D by observation of the occupational therapist and interviews with family members. Basic information and the scores of BADL items of the PADA‐D were compared between the three groups. Subsequently, we compared the percentage of independent or non‐independent processes included in the sub‐items of BADL in the PADA‐D. Results: A total of 143 patients were included in the analysis. Performance on BADL was shown to decrease significantly with increasing severity of cognitive impairment. The percentage of all BADL processes performed ranged from 58% to 100% in mild, 38% to 97% in moderate, and 0% to 88% in severe. Some of the processes included in BADL of PADA‐D showed no significant differences in independence between the three groups. Discussion/Conclusion: Most BADL processes differed with respect to different independence rates depending on the severity of cognitive impairment of the older adults with dementia. However, some BADL processes were not associated with the severity of cognitive impairment. Our findings may suggest that a detailed BADL assessment of patients with dementia is useful in terms of caregiver education to avoid excessive caregiving and in predicting BADL impairment.